PEMENUHAN KEBUTUHAN INFORMASI OLEH LINE TODAY PADA PEMUDA DI KOTA DENPASAR - Purwaningsih, Ni Putu Indriana; Amanda Gelgel, Ni Made Ras; Alit Suryawati, I Gusti Agug (E-Jurnal Medium; Vol 1 No 1 (2019), 2019)
ABSTRACT                  LINE TODAY is a feature that created by the LINE application for LINE users to find information on a daily basis.LINE TODAY has various types of news, namely news, entertainment, biz & tech, and lifestyle. This study aims to find out how information fulfillment by LINE TODAY on youth in Denpasar City.This study used the theory of Uses and Gratifications. The method used is descriptive quantitative with sampling technique is purposive sampling. Data obtained by using a Likert scale in the questionnaire.The results of this study showed, LINE TODAY has not been able to fulfillment the information needs of the youth in Denpasar City.   Keywords : Information,LINE TODAY, Motive, Satisfaction